USE OF BILATERAL MIDDLE CEREBRAL ARTERY BLOOD FLOW MONITORING WITH MICROEMBOLI DETECTION FOR EARLY VERIFICATION OF FAT EMBOLISM SYNDROME IN POLYTRAUMA - Воронкин, Роман Геннадьевич; Баранов, Владимир Алексеевич; Баранова, Наталья Андреевна; Автушенко, Никита Васильевич; Чуднов, Алексей Евгеньевич; Кричевский, Лев Анатольевич (Medicine in Kuzbass, 2025)
Fat Embolism Syndrome (FES), as defined by several authors, is a severe, life-threatening condition caused by multiple occlusions of blood vessels with fat droplets-fat emboli-consisting of undifferentiated lipid masses, adipocytes, or lipid complexes larger than 6-8 μm [1-4]. It develops during the early stages of traumatic disease or sometime after surgical intervention related to trauma correction [2, 5-7]. Unfortunately, there is still no «gold standard» for diagnosing FES, making the search for new visual diagnostic methods highly relevant. A clinical case is presented demonstrating the visual diagnosis of FES using a non-invasive technique of bilateral transcranial Doppler (TCD) monitoring of middle cerebral artery (MCA) flow with microemboli detection via an ultrasound transcranial Doppler analyzer in a 74-year-old patient following corrective osteotomy and titanium plate fixation for a malunited fracture of the proximal right femur.